Generalized Measure of Fuzzy Entropy in Various Parameter - Pandey, Sangeeta; Dubey, RP; Jha, P (International Journal of Computer Sciences and Engineering, 2025)
In the present paper, the fuzzy entropy measures are obtained by existing literatures. A generalized parametric fuzzy entropy in various parameter is defined. Fuzziness is one of the pandemic attributes of human thinking and objectives things whereas fuzzy set theory is one of the effective tools of researching and processing fuzzy phenomena in real world’s problems. Taking this fact into contemplate, we have introduced and investigated new generalized measure of fuzzy entropy based upon real parameters, studied their fundamental and desirable properties and presented these measures through graph